A Preliminary Investigation of Complexity Theory’s Potential to Redefine and Reinvigorate the Field of Adult Education - Jeff Zacharakis (Adult Education Research Conference, 2022)
Complex adaptive systems inherently fill niches, as one niche is filled another niche is created, hence these systems are never stable. This roundtable explores utilizing complexity theory to reimagine the future of adult education graduate programs.
Keywords: complexity theory; adult education; graduate programs